2022
DOI: 10.1038/s41409-022-01823-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related quality of life in patients with β-thalassemia after unrelated hematopoietic stem cell transplantation

Abstract: Long-term health-related quality of life in patients with β-thalassemia after unrelated hematopoietic stem cell transplantation. Bone marrow transplantation, 57(12), 1833-1836.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In one study that examined the pediatric beta‐thalassemia patient population in Italy, HSCT was associated with a higher total PedsQL score and emotional functioning, physical functioning, and school functioning domain scores 40 . In this study, there was no significant difference in HRQOL between patients who received sibling versus unrelated HLA‐matched HSCT 36,39,40 . However, another study showed QOL was higher when transplantation occurred from a voluntary donor compared to an HLA‐mismatched related donor 46 …”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…In one study that examined the pediatric beta‐thalassemia patient population in Italy, HSCT was associated with a higher total PedsQL score and emotional functioning, physical functioning, and school functioning domain scores 40 . In this study, there was no significant difference in HRQOL between patients who received sibling versus unrelated HLA‐matched HSCT 36,39,40 . However, another study showed QOL was higher when transplantation occurred from a voluntary donor compared to an HLA‐mismatched related donor 46 …”
Section: Resultsmentioning
confidence: 54%
“…40 In this study, there was no significant difference in HRQOL between patients who received sibling versus unrelated HLA-matched HSCT. 36,39,40 However, another study showed QOL was higher when transplantation occurred from a voluntary donor compared to an HLA-mismatched related donor. 46 When examining the impact of beti-cel gene therapy on patients with TDT enrolled in phase 3 studies who reached transfusion independence, patients reported improvement in HRQOL for physical and mental component summary scores using the SF-36 and the total score on the PedsQL.…”
Section: Curative Therapies In Tdtmentioning
confidence: 50%
See 1 more Smart Citation
“…A possible role of splenectomy in improving the allogeneic hematopoietic stem cell transplantation (HSCT) outcome has also been explored. Although faster neutrophil engraftment was observed, this did not produce significantly better overall survival rates after HSCT and did not provide any advantages [ 9 , 15 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of randomized and quasi-randomized controlled studies was unable to find good-quality evidence about the efficacy of splenectomy for treating β-TM [ 12 ]. Among the parameters used to evaluate the patient’s wellness in a chronic disease such as β-TM, health-related quality of life (HRQoL) plays a key role [ 13 , 14 , 15 ]. HRQoL is generally conceptualized as a multidimensional construct referring to patients’ perceptions of the impact of disease and treatment on their physical, psychological, and social functioning and well-being [ 16 ].…”
Section: Introductionmentioning
confidence: 99%